Pietų Lietuvos vėlyvieji degintiniai kapinynai - Zabiela, Gintautas (Archaeologia Lituana, 2003)
To date, 18 sites are known in the southern region of lithuania (including the present territory of Belarus) where remains of late cremation burials have been found (fig. 1). These data give a possibility for a more reliable consideration of the grouping of late cremation cemeteries in southern Lithuania than 5 years ago (Zabiela, 1998a). Their burial pattern is specified on the basis of two cemeteries, namely Rumšiškės and Žėronys. In 1953 as many as 21 sites of disturbed cremation graves (fig. 2) were recorded at the Rumšiškės cremation cemetery, while during excavations in 1963, 5 further conspicuous cremation graves (table 1) were investigated at the site of a 14th–16th century cemetery. All the cremation graves at the old cemetery of Rumšiškės were very shallow, the grave pits were up to 20 cm deep. The grave pits were oval, measuring from 70 x 55 to 130 x 100 cm, tapering towards the bottom. A characteristic feature of cremation graves is abundant finds of wheel-made pottery. The grave goods include details of apparel and remains of ornaments (fig. 3).More details for further insight into cremation cemeteries of southern Lithuania were revealed at the Žėronys cemetery excavated to some extent by the author of the present article in 1996. An area of just 12.5 sq m was excavated at the cemetery, the major part of which had been damaged by a pit dug by fortune seekers. The Žėronys cemetery was set up in the central part of a mound with an uneven surface, 7 m high and approximately 70 x 20 m in size (fig. 4). The excavations showed that the cemetery occupied an area which was 20 m in diameter, while the mound itself had never been ploughed. The majority of cremation graves were uncovered right under the turf, no deeper than 20 cm from the ground surface. Burnt bones and scorched grave goods were carefully assembled and deposited into a shallow pit dug in the sand. Remains of cremation burials were deposited into pits at the cemetery rather densely and slightly scattered. During the excavations, remains of 7 assumed cremation graves were identified (fig. 5) (table 2). The grave goods almost exclusively consist of metal parts of apparel, such as bell buckles, mountings, loops, rivets and scarce working tools, such as knives, awls, needles, razors, firesteels, and ornaments like rings and a tinkler. The abundant assemblage of pottery (946 sherds) belongs to slightly wheel-turned jars with blown sides, a profiled neck and an outwards flared rim. Quite a number of pats were decorated with patterns of parallel lines, waves and rollers imitating twisting (fig. 6).The late cremation cemeteries of southern Lithuania are widespread in the territory which was previously covered by east Lithuanian barrows and later on by old mediaeval cemeteries. South Lithuanian cremation cemeteries are dated to the 13th–14th centuries. 13th century cremation graves have been also found at the Ašmenėlis and Stakai barrow cemeteries. They could have been dug into barrows piled earlier and used for burial, but disturbed earth piles do not allow proving this. Meanwhile, cremation graves dated to the 11th century should be interpreted as remains of destroyed late barrows, even though they were not found at barrow cemeteries (e. g. Bagrėnas (fig. 7), Perloja). Search for small-scale cremation cemeteries should in the future be focused on the surroundings of such barrows.Cremation cemeteries must be the legacy of ordinary commoners father than warriors, as is sometimes said. This is testified by grave goods from these burials, which do not include more weapons or other articles attributable to warriors than earlier or later graves. A survey of other archaeological sites in the neighbourhood of cremation cemeteries does not reveal any relationship between them and larger defence centres.